A Hands-On Exercise on Caries Diagnostics among Dental Students—A Qualitative Study - Heidi Kangas; Saujanya Karki; Tarja Tanner; Anne Laajala; Helvi Kyngäs; Vuokko Anttonen (Dentistry Journal, 2021)
According to current care practices, the aim is to prevent the onset of caries lesions and to stop the progression of incipient lesions. A visual lesion assessment system, International Caries Detection and Assessment System (ICDAS), has been developed to promote reliability and repeatability of assessment of different stage caries lesions. The aims of this study were to evaluate the experiences of a hands-on exercise with authentic teeth as an adjunct to lecturing among third-year dental students and to evaluate the learning process during the hands-on exercise measured by qualitative (inductive content) analysis of the given feedback. In 2018, 51 third-year dental students at the University of Oulu, Finland, participated in a hands-on exercise on caries detection, where they assessed the depth and activity of lesions in extracted teeth using the ICDAS classification. After the lecture, students evaluated the exercise, giving feedback according to five given topics, three of which were analyzed using inductive content analysis. The exercise was considered useful and necessary but, overall, also challenging. The diverse activities and materials, as well as observational methods, promoted learning. The classification of lesions, the diagnostic methods, and the fact that there was not enough time to adopt things during the exercise were found to be challenging. For developing the exercise, the students suggested that more time should be scheduled for it and there should be more individual teaching. This qualitative study showed that, despite the challenge in caries diagnostics, dental students perceive the hands-on exercise as both a communal and individual learning experience.